2020
DOI: 10.1177/0192623320932159
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 10 Urinary Biomarkers for Renal Safety With 5 Nephrotoxicants in Nonhuman Primates

Abstract: To date, there has been very little published data evaluating the performance of novel urinary kidney biomarkers in nonhuman primates (NHPs). To assess the biomarker performance and characterize the corresponding histomorphologic patterns of tubular renal injury in the NHP, several studies were conducted using mechanistically diverse nephrotoxicants including cefpirome, cisplatin, naproxen, cyclosporine, and a combination of gentamicin with everninomicin. An evaluation of 10 urinary biomarkers (albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…Also, the methodology presented here could be extended to other biomarkers (eg, cystatin C, β2 microglobulin), a broader spectrum of lesions, other tissues, or even other different contexts, either in toxicology or in general pathology (eg, other tissues, disease markers, genetic abnormalities, etc). 24,25,36…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the methodology presented here could be extended to other biomarkers (eg, cystatin C, β2 microglobulin), a broader spectrum of lesions, other tissues, or even other different contexts, either in toxicology or in general pathology (eg, other tissues, disease markers, genetic abnormalities, etc). 24,25,36…”
Section: Discussionmentioning
confidence: 99%
“…Also, the methodology presented here could be extended to other biomarkers (eg, cystatin C, b2 microglobulin), a broader spectrum of lesions, other tissues, or even other different contexts, either in toxicology or in general pathology (eg, other tissues, disease markers, genetic abnormalities, etc). 24,25,36 The ability of MIL to identify relatively small regions of the slides (in our case squares of 224 mm  224 mm) associated with the elevation of a particular biomarker has the potential to facilitate the characterization of precursor lesions. This would apply also to the detection of particular combinations of elementary lesions associated with the elevation of a biomarker, thereby facilitating its phenotypic anchoring.…”
Section: Weakly Supervised Learning Enables Localization and Interpretability At The Tile Levelmentioning
confidence: 99%
“…[190][191][192] Numerous rodent DIKI studies demonstrated the utility of urinary KIM-1 for detection of AKI, 47,52,77,[193][194][195][196][197][198][199] but performance of urinary KIM-1 in nonrodent species has been less consistent. Early increases in urine KIM-1 were seen in some AKI studies in monkeys 45,48,196,200 but not in others. 201 In the dog, some authors describe diagnostic utility for KIM-1, 202,203 while others, including the current authors, report poor accuracy of KIM-1 in dog DIKI studies.…”
Section: Kidney Injury Moleculementioning
confidence: 91%
“…58 AKI marker with a large dynamic range in many species. 40,48,59,60 Good at predicting the progression of AKI to CKD. 61 Systemic inflammation or sepsis can cause increased serum levels which can lead to increased urine levels in the absence of renal injury.…”
Section: Estimated Gfrmentioning
confidence: 99%
See 1 more Smart Citation